Is tonsillectomy mandatory for asymmetric tonsils in children? A review of our diagnostic tonsillectomy practice and the literature. (July 2018) - Jones, Gareth Huw; Burnside, Girvan; McPartland, Jo; Markey, Anne; Fallon, Michael; De, Sujata
Abstract: Introduction: Diagnostic tonsillectomy is performed to exclude malignancy. It is associated with a post-operative hemorrhage rate of 3.5%, (1) which is more dangerous in small children. No previous case series for asymmetrical tonsils have detected tonsil lymphoma.(2–6) We aimed to review our local diagnostic tonsillectomy practice. Method: The authors reviewed the clinical notes and histological results for all diagnostic tonsillectomies carried out from June 2013 to June 2016. Results: We recorded data for 168 patients. There were four post-operative bleeds and one return to theatre. Bilateral tonsillectomies accounted for 152 operations (90.5%). Lymphoid hyperplasia accounted for 95% of histological diagnosis with no malignancies found. Pre-operative tonsil grading demonstrated no statistically significant association with histological tonsil weight difference (ANOVA p = 0.10). Actinomyces colonisation had little affect on tonsil weight difference when we compared patients with bilateral colonisation and no colonisation ( t -test p = 0.540) and between tonsils in patients with unilateral tonsil Actinomyces colonisation (paired t -test p = 0.448). Recurrent tonsillitis was more prevalent in patients with Actinomyces colonisation than OSA/sleep disordered breathing (39% vs 15%). Conclusion: A literature search yielded five smaller case series of palatine tonsil asymmetry in children with no malignancy found.(2–6) Case-control studies report tonsillar asymmetry as the most common presenting symptom (73%) in tonsillar lymphoma.(7) This enlargement usually occurs rapidly within 6 weeks with new obstructive or systemic B-type symptoms.(3) A Turkish epidemiological study found asymmetrical tonsils in 1.7% of the healthy paediatric population.(8) We therefore estimate there to be over 210, 000 children with asymmetrical tonsils in the UK. With an unreliable grading system, we believe asymmetrical tonsils in isolation, unchanged for over 6 weeks may not warrant tonsillectomy.